2021
DOI: 10.3389/fendo.2021.609771
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Long GnRH Agonist Protocol During IVF/ICSI Improves Pregnancy Outcomes in Women With Adenomyosis: A Retrospective Cohort Study

Abstract: ObjectiveThis study aimed to compare the ultra-long gonadotropin-releasing hormone agonist (GnRH-a) protocol and the long GnRH-a protocol during in vitro fertilization (IVF) or intracytoplasmic sperm (ICSI) treatment on fertility outcomes in women with adenomyosis.Materials and MethodsThis study was a retrospective cohort study. From January 2011 to May 2018, a total of 371 fresh IVF/ICSI cycles were included. Among the cycles included, 237 cycles of 212 women underwent the ultra-long GnRH-a protocol, while 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…GnRH modulators may improve reproductive outcomes among women with adenomyosis undergoing IVF. In a large retrospective cohort, pretreatment with an ultra-long GnRH-agonist (2–4 months prior to embryo transfer) compared with a long GnRH-agonist (single dose given in the preceding cycle luteal phase prior to ovarian stimulation) improved the live birth rate, 43 vs. 26%, P = 0.019, and clinical pregnancy rate, 55 vs. 38%, P = 0.025 [31 ▪ ]. In a similar retrospective cohort, an ultra-long GnRH agonist protocol compared with a long agonist protocol was also associated with increased live birth rate and clinical pregnancy rate with fresh transfer [32 ▪ ].…”
Section: Treatment Of Adenomyosis For Patients With Infertilitymentioning
confidence: 99%
“…GnRH modulators may improve reproductive outcomes among women with adenomyosis undergoing IVF. In a large retrospective cohort, pretreatment with an ultra-long GnRH-agonist (2–4 months prior to embryo transfer) compared with a long GnRH-agonist (single dose given in the preceding cycle luteal phase prior to ovarian stimulation) improved the live birth rate, 43 vs. 26%, P = 0.019, and clinical pregnancy rate, 55 vs. 38%, P = 0.025 [31 ▪ ]. In a similar retrospective cohort, an ultra-long GnRH agonist protocol compared with a long agonist protocol was also associated with increased live birth rate and clinical pregnancy rate with fresh transfer [32 ▪ ].…”
Section: Treatment Of Adenomyosis For Patients With Infertilitymentioning
confidence: 99%
“…Two studies concluded that conservative surgery combined with GnRH agonist, rather than GnRH agonist alone, is able to improve symptoms and boost reproductive potential in adenomyosis patients [ 90 , 91 ]. Finally, an ultra-long GnRH protocol before ovarian stimulation appears to yield better pregnancy outcomes than the corresponding long protocol [ 92 , 93 ]. More specifically, one study reported significantly higher pregnancy and live birth rates in patients with diffuse adenomyosis receiving a 3.75 mg dose of diphereline subcutaneously on a monthly basis for 2–4 months prior to stimulation compared to corresponding patients receiving a single 0.93–1.87 mg dose on the 18th–20th day [ 92 ].…”
Section: Medical Treatment Of Adenomyosismentioning
confidence: 99%
“…Finally, an ultra-long GnRH protocol before ovarian stimulation appears to yield better pregnancy outcomes than the corresponding long protocol [ 92 , 93 ]. More specifically, one study reported significantly higher pregnancy and live birth rates in patients with diffuse adenomyosis receiving a 3.75 mg dose of diphereline subcutaneously on a monthly basis for 2–4 months prior to stimulation compared to corresponding patients receiving a single 0.93–1.87 mg dose on the 18th–20th day [ 92 ]. Consistent with these findings, a second study reported a significant increase in rates of both clinical pregnancy and live births in adenomyosis patients pre-treated with triptorelin (3.75 mg) intramuscularly every 28 days for at least 3 months, compared with 0.1 mg/day dose for 10 days [ 93 ].…”
Section: Medical Treatment Of Adenomyosismentioning
confidence: 99%
“…It was noted that an essential part of full-dose GnRH-a is involved in the improvement of follicular synchronization and endometrial receptivity. As a consequence, this prolonged downregulation before controlled ovarian hyperstimulation (COH) and embryo transfer (ET) might be acceptable in patients with endometriosis [9], adenomyosis [10,11], and a general cohort [12,13]. However, several studies have been performed to compare outcomes between the depot GnRH-a protocol and long protocol, with different conclusions presented regarding Gn doses, the duration of stimulation, the number of retrieved oocytes, fertilization rates, and pregnancy rates [1,6,[13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%